THE ROLE OF CORPORATE GOVERNANCE STRUCTURE IN COMPLIANCE LEVEL OF MANDATORY DISCLOSURE AFTER IFRS CONVERGENCE (Study on Manufacturing Companies Listed on the Indonesia Stock Exchange) - Barbara Gunawan; Eka Riana Hendrawati (Berkala Akuntansi dan Keuangan Indonesia, 2016)
This study aims to examine the level of mandatory disclosure compliance in the period after IFRS convergence in manufacturing companies listed on the Indonesia Stock Exchange. Researchers also examine the effect of corporate governance mechanisms on the level of compliance with mandatory disclosure. The corporate governance mechanism is measured by the number of members of the board of commissioners, managerial ownership, the proportion of independent commissioners, the background of the main commissioners, the proportion of female commissioners, and the number of audit committee members. Data collection using purposive sampling method on companies listed on the Indonesia Stock Exchange in 2012 and 2013. The sample used is 36 companies. The results show that the variables of corporate governance mechanism that affect the level of compliance with the convergence of IFRS mandatory disclosure are the number of independent commissioners and the number of members of the audit committee. The managerial ownership variables, the proportion of independent commissioners, the background of the commissioners, and the proportion of female commissioners have no effect on the level of compliance with mandatory disclosure in the period after IFRS convergence.